Switching device
The switch device with a composite structure of specific thickness and layer configuration effectively mitigates heating and unevenness issues, ensuring reliable operation and maintaining flatness even under heat exposure.
Patent Information
- Application Number
- JP2023168508
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-09
AI Technical Summary
The existing switch devices with glass and resin layers face issues of heating and unevenness due to size differences in the layers during heating, leading to deformation and loss of flatness.
A switch device is designed with a composite structure comprising a first glass layer, a resin layer, and a second glass layer, where the total thickness of the composite is 230 μm or less, and the composite is elastically deformed to switch the switch between conduction and non-conductivity.
This configuration significantly reduces the likelihood of heating and unevenness in the composite, allowing for reliable elastic deformation and proper functioning of the switch, even under heat exposure.
Smart Images

Figure 2025058523000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a switch device. [Background technology]
[0002] A switch device is known that has a composite of a glass layer and a resin layer and a switch disposed on the underside of the resin layer of the composite, in which the composite is elastically deformed when pressed, switching the switch between conductive and non-conductive states. In this switch device, the switch is disposed inside an opening provided in a support, and the composite is disposed on the support outside the opening. In the support, the boundary between the inside and outside of the opening has an uneven shape. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2022-166480 A Summary of the Invention [Problem to be solved by the invention]
[0004] In a composite of a glass layer and a resin layer, the dimensional changes when heated are different for each layer, and since general resins tend to shrink when heated, the composite may deform along the opening when heated, resulting in unevenness. This unevenness is called heat unevenness.
[0005] An object of the present invention is to provide a switch device in which unevenness due to heating is unlikely to occur in a composite body including a glass layer and a resin layer. [Means for solving the problem]
[0006] This switch device comprises a composite including a first glass layer, a resin layer laminated on the underside of the first glass layer, and a second glass layer laminated on the underside of the resin layer; a support portion disposed on the underside of the second glass layer of the composite, having an opening and supporting the composite outside the opening; and a switch, at least a portion of which is disposed inside the opening, wherein a total thickness of the composite is 230 μm or less. When the composite is pressed, the composite elastically deforms, switching the switch between conductive and non-conductive states. Effect of the Invention
[0007] According to the disclosed technique, it is possible to provide a switch device in which the composite body including a glass layer and a resin layer is less likely to develop unevenness due to heating. [Brief description of the drawings]
[0008] [Figure 1] 1 is a cross-sectional view illustrating a switch device according to a first embodiment. [Diagram 2] 5A to 5C are diagrams illustrating the operation of the switch device according to the first embodiment. [Diagram 3] FIG. 1 is a diagram illustrating an example, a comparative example, and a reference example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In the drawings, the same components are denoted by the same reference numerals, and duplicated explanations may be omitted.
[0010] First embodiment Fig. 1 is a cross-sectional view illustrating a switch device according to a first embodiment. As shown in Fig. 1, the switch device 1 includes a composite 10, a bonding layer 20, a support 30, and a switch 40. The composite 10 also includes a first glass layer 11, a resin layer 12 laminated on the lower surface side of the first glass layer 11, and a second glass layer 13 laminated on the lower surface side of the resin layer 12.
[0011] The components of the switch device 1 will be described below.
[0012] [First glass layer] The first glass layer 11 has an upper surface 11a and a lower surface 11b opposite to the upper surface 11a. The upper surface 11a is a single continuous surface. The lower surface 11b is also a single continuous surface. The upper surface 11a side of the first glass layer 11 becomes the outermost surface of the switch device 1. The first glass layer 11 preferably has high surface durability represented by a pencil hardness test of 9H or more and excellent dimensional stability.
[0013] The first glass layer 11 is not particularly limited, and an appropriate material can be adopted depending on the purpose. The first glass layer 11 can be classified according to composition, for example, soda-lime glass, borate glass, aluminosilicate glass, quartz glass, etc. Also, according to alkali components, it can be non-alkali glass or low-alkali glass. The content of alkali metal components (for example, Na2O, K2O, Li2O) in the above glass is preferably 15 wt% or less, more preferably 10 wt% or less.
[0014] Considering the surface hardness, airtightness, and corrosion resistance of glass, the thickness of the first glass layer 11 is preferably 20 μm or more. Since the first glass layer 11 needs to have flexibility and durability for repeated use like a film, the thickness of the first glass layer 11 is preferably 150 μm or less. The thickness of the first glass layer 11 is more preferably 50 μm to 150 μm, even more preferably 30 μm to 120 μm, and particularly preferably 50 μm to 100 μm.
[0015] The first glass layer 11 preferably has a light transmittance of 85% or more at a wavelength of 550 nm. The first glass layer 11 preferably has a refractive index of 1.4 to 1.65 at a wavelength of 550 nm. The first glass layer 11 preferably has a density of 2.3 g / cm 3 ~3.0g / cm 3 and more preferably 2.3 g / cm 3 ~2.7g / cm 3 It is.
[0016] The method for forming the first glass layer 11 is not particularly limited, and an appropriate method can be adopted depending on the purpose. Typically, the first glass layer 11 can be produced by melting a mixture containing a main raw material such as silica or alumina, an antifoaming agent such as mirabilite or antimony oxide, and a reducing agent such as carbon at a temperature of about 1400°C to 1600°C, forming it into a thin plate, and then cooling it. Examples of the method for forming the first glass layer 11 include a slot downdraw method, a fusion method, and a float method. The glass layer formed into a plate by these methods may be chemically polished with a solvent such as hydrofluoric acid as necessary to make it thinner or to increase the smoothness.
[0017] The first glass layer 11 may be made of tempered glass. The tempered glass may be chemically tempered glass or thermally tempered glass, but chemically tempered glass having a compressive stress layer is easier to manufacture than thermally tempered glass. When the first glass layer 11 is made of tempered glass, it is preferable that the compressive stress is 600 MPa or more.
[0018] Chemical strengthening refers to replacing ions near the surface of a glass sheet with ions with a larger ionic radius. The ion exchange forms a compressive stress layer on the surface of the glass sheet, resulting in chemically strengthened glass. The glass composition in the compressive stress layer is different from the glass composition inside the glass.
[0019] In the chemically strengthened glass, the glass plate before strengthening can be, for example, soda-lime glass, aluminosilicate glass, borosilicate glass, aluminoborosilicate glass, etc. In that the depth of the compressive stress layer does not become too large more than necessary, soda-lime glass or soda-silicate glass is preferable, and soda-lime glass is more preferable.
[0020] Ion exchange can be carried out, for example, by substituting Li ions on the surface of the glass sheet with Na ions and / or K ions. Alternatively, Na ions on the surface of the glass sheet may be substituting K ions. By such ion exchange, a compressive stress layer is formed on the surface of the glass sheet.
[0021] When Na ions are replaced with K ions, for example, a glass plate containing sodium may be brought into contact with an inorganic molten salt containing potassium nitrate. The inorganic molten salt containing potassium nitrate preferably contains at least one salt selected from the group consisting of K2CO3, Na2CO3, KHCO3, NaHCO3, KOH, and NaOH.
[0022] A functional layer such as an antifouling layer, an antireflection layer, a conductive layer, a reflective layer, a decorative layer, etc. may be provided on the upper surface 11a and / or the lower surface 11b of the first glass layer 11. Braille may also be provided on the upper surface 11a of the first glass layer 11. In the switch device according to this embodiment, the first glass layer 11 is located at the top surface. Here, "the first glass layer 11 is located at the top surface" means that the first glass layer 11 is substantially located at the top surface, and even if an additional layer as described above is provided, in this embodiment, it is expressed that the first glass layer 11 is located at the top surface.
[0023] [Resin layer] The resin layer 12 is laminated on the lower surface 11b side of the first glass layer 11. The resin layer 12 has an upper surface and a lower surface that is the surface opposite to the upper surface. The resin layer 12 is flexible. From the viewpoint of flexibility, the thickness of the resin layer 12 is preferably 20 μm or more and 150 μm or less, and more preferably 25 μm or more and 100 μm or less.
[0024] Examples of materials for the resin layer 12 include polyester-based resins such as polyethylene terephthalate-based resins and polyethylene naphthalate-based resins, cycloolefin-based resins such as norbornene-based resins, polyethersulfone-based resins, polycarbonate-based resins, acrylic-based resins, polyolefin-based resins, polyimide-based resins, polyamide-based resins, polyimideamide-based resins, polyarylate-based resins, polysulfone-based resins, polyetherimide-based resins, and urethane-based resins.
[0025] [Second glass layer] The second glass layer 13 is laminated on the lower surface side of the resin layer 12. The second glass layer 13 has an upper surface and a lower surface that is the surface opposite to the upper surface. Details of the second glass layer 13 are the same as those of the first glass layer 11 already described. The first glass layer 11 and the second glass layer 13 may be formed of the same material or different materials. The first glass layer 11 and the second glass layer 13 may have the same thickness or different thicknesses. From the viewpoint of flexibility and repeated durability, the thickness of the second glass layer 13 is preferably 150 μm or less. The thickness of the second glass layer 13 is more preferably 50 μm or more and 100 μm or less, and particularly preferably 30 μm or more and 50 μm or less.
[0026] The thickness of the second glass layer 13 is preferably equal to or less than the thickness of the first glass layer 11. With such a thickness relationship, the resistance of the second glass layer 13 to indentation deformation of the composite 10 can be kept low.
[0027] A bonding layer may be provided between the lower surface 11b of the first glass layer 11 and the upper surface of the resin layer 12. Also, a bonding layer may be provided between the upper surface of the second glass layer 13 and the lower surface of the resin layer 12. Any adhesive or bonding material described below may be used as the bonding layer. However, from the viewpoint of strength, it is preferable to use an adhesive as the bonding layer. From the viewpoint of appearance, the thickness of the bonding layer is preferably 0.5 μm or more and 25 μm or less, more preferably 0.5 μm or more and 5 μm or less, and even more preferably 0.5 μm or more and 3 μm or less.
[0028] A plurality of resin layers may be laminated on the lower surface 11b side of first glass layer 11. Such a laminated structure can suppress cracking of first glass layer 11 and improve the durability of first glass layer 11 when it is repeatedly elastically deformed.
[0029] [Joining layer] The bonding layer 20 bonds the second glass layer 13 and the supporting part 30 of the composite 10. Any adhesive or adhesive can be used as the bonding layer 20. The thickness of the bonding layer 20 can be, for example, 5 μm or more and 20 mm or less.
[0030] In this specification, a pressure-sensitive adhesive refers to a layer that has adhesive properties at room temperature and adheres to an adherend with light pressure. Therefore, even when an adherend that has been stuck to the pressure-sensitive adhesive is peeled off, the pressure-sensitive adhesive retains practical adhesive strength. On the other hand, an adhesive refers to a layer that can bond substances by being interposed between them. Therefore, when an adherend that has been stuck to the adhesive is peeled off, the adhesive no longer has practical adhesive strength.
[0031] Examples of the adhesive include adhesives having, as a base polymer, an acrylic polymer, a silicone polymer, a polyester, a polyurethane, a polyamide, a polyether, a fluorine-based polymer, a rubber-based polymer, or the like.
[0032] Examples of adhesives include polyester adhesives, polyurethane adhesives, polyvinyl alcohol adhesives, and epoxy adhesives. When the adhesive is a thermosetting adhesive, it can be heated to harden (solidify) and exert its peel resistance. When the adhesive is a photocurable adhesive such as an ultraviolet-curable adhesive, it can be hardened by irradiating it with ultraviolet light or other light and exert its peel resistance. When the adhesive is a moisture-curable adhesive, it can be hardened by reacting with moisture in the air, and can be hardened by being left to stand and exert its peel resistance.
[0033] [Support part] The supporting part 30 is disposed on the lower surface side of the second glass layer 13 of the composite body 10. The supporting part 30 has, for example, a rectangular shape in a plan view. The supporting part 30 may have a shape other than a rectangular shape in a plan view. The supporting part 30 can be formed from, for example, a resin or a metal.
[0034] The support 30 has an opening 30x and supports the composite 10 outside the opening 30x. The opening 30x is, for example, circular in plan view. In the example of FIG. 1, the opening 30x is a recess that opens on the upper surface side (the second glass layer 13 side) of the support 30. In the example of FIG. 1, the opening 30x exposes the lower surface of the second glass layer 13. Note that the cross-sectional view of FIG. 1 shows a cross section cut along a plane that passes through the center of the opening 30x and is perpendicular to the upper surface of the support 30.
[0035] The support section 30 may have a plurality of openings 30x spaced apart from one another. The plurality of openings 30x may be arranged, for example, in a matrix in plan view. A switch 40 may be arranged in each of the openings 30x. Furthermore, one complex 10 may be arranged so as to cover the plurality of openings 30x.
[0036] [switch] The switch 40 is a switch that detects a physical change when pressed. At least a portion of the switch 40 is disposed inside the opening 30x of the support portion 30. By operating the switch 40, a clicking sensation is obtained. In the example of FIG. 1, the switch 40 is a tactile switch that is disposed such that a movable portion faces the lower surface of the second glass layer 13.
[0037] Switch 40 is not limited to a tactile switch, and may be any switch that provides a clicking sensation, such as a membrane switch. When switch 40 is a membrane switch, two sheets are arranged opposite each other to form a space that serves as an opening, and two terminals are arranged vertically opposite each other within the opening. In other words, when switch 40 is a membrane switch, a member that constitutes the switch serves as a support, and a part of the member that constitutes the switch (two terminals) is arranged within the opening of the support.
[0038] A member that is movable in the vertical direction independently of the composite 10 may be sandwiched between the switch 40 and the lower surface of the second glass layer 13. This member is supported by the support portion 30 in a state in which it is movable in the vertical direction, for example, via a spring or the like. When the composite 10 is pressed, the composite 10 elastically deforms and presses the member, thereby switching the switch between conductive and non-conductive states.
[0039] 1, a gap is provided between the lower surface of the second glass layer 13 and the movable part of the switch 40, but the gap need not be provided. Also, a mechanism for transmitting deformation of the composite 10 to the switch 40 may be provided between the switch 40 and the second glass layer 13. It is preferable that the switch device 1 has a gap large enough that the switch 40 does not interfere with the flatness of the first glass layer 11 and the second glass layer 13. However, it is preferable to have a gap large enough to allow the composite 10 to operate when pressed down by 1 mm or less.
[0040] Fig. 2 is a diagram for explaining the operation of the switch device according to the first embodiment. As shown in Fig. 2, in the switch device 1, when the complex 10 is pressed in the direction of the arrow, the complex 10 elastically deforms and presses the movable part of the switch 40, switching between conductive and non-conductive states of the switch 40. When pressing the complex 10 is stopped, the complex 10 and the switch 40 return to the state shown in Fig. 1.
[0041] In the switch device 1, the total thickness of the composite 10 is preferably 230 μm or less, and more preferably 205 μm or less. When the total thickness of the composite 10 is 230 μm or less, the composite 10 is less likely to have unevenness due to heating. That is, when the switch device 1 is placed in a heated environment of, for example, about 60 ° C., when the total thickness of the composite 10 is 230 μm or less, unevenness along the edge of the opening 30x is less likely to occur in the composite 10. This makes it possible to suppress a decrease in the flatness of the composite 10. Furthermore, when the total thickness of the composite 10 is 205 μm or less, the composite 10 is even less likely to have unevenness due to heating. That is, when the total thickness of the composite 10 is 205 μm or less, when the switch device 1 is placed in a heated environment of, for example, about 60 ° C., unevenness along the edge of the opening 30x is even less likely to occur in the composite 10. This makes it possible to further suppress a decrease in the flatness of the composite 10.
[0042] Furthermore, if the total thickness of composite 10 is 205 μm or less, it will be possible for composite 10 to repeatedly deform elastically and push in the movable portion of switch 40 so that switch 40 alternates between conductive and non-conductive states.
[0043] Examples, Comparative Examples, and Reference Examples The inventors have considered a composite in which a glass layer is provided under a resin layer in a laminate of a glass layer and a resin layer to maintain the surface hardness of the glass layer while preventing deformation due to heat. However, if a glass layer is simply provided under a resin layer, the shear stress of the composite increases due to the glass layers above and below the resin layer in response to deformation caused by pressing a switch, which causes a problem that the switch cannot be pressed. Therefore, the inventors have investigated a switch device that does not generate unevenness due to heat and allows the switch to be pressed.
[0044] [Example 1] (First glass layer) A glass film (OA-10, manufactured by Nippon Electric Glass Co., Ltd.) having a thickness of 100 μm was cut into a 10 cm square to form a first glass layer.
[0045] (2nd glass layer) A glass film (OA-10, manufactured by Nippon Electric Glass Co., Ltd.) having a thickness of 50 μm was cut into a 10 cm square to serve as a second glass layer.
[0046] (Preparing the adhesive) An adhesive solution was prepared by mixing an epoxy resin (Celloxide 2021P, Daicel Chemical Industries, Ltd.), an oxetane resin (Aron Oxetane OXT-221, Toa Gosei Co., Ltd.), a polymerization initiator (Adeka Optomer SP-170, ADEKA Corporation), and a coupling agent (KBM-403, Shin-Etsu Chemical Co., Ltd.) in a ratio of 90:10:3:2.
[0047] (Preparation of resin film) As a resin film to be the resin layer, a PET film (Cosmoshine A4160, manufactured by Toyobo Co., Ltd.) having a thickness of 50 μm was prepared.
[0048] (Preparation of Complex) An adhesive was applied to both sides of the resin film to a thickness of 5 μm to form a coating layer. Then, a first glass layer was laminated on the upper surface of the coating layer, and a second glass layer was laminated on the lower surface of the coating layer. After that, ultraviolet light was irradiated from a high-pressure mercury lamp (wavelength: 365 nm, intensity: 1000 mJ / cm 2 The coating layer was cured by the above steps to obtain a composite of the first glass layer, the resin layer, and the second glass layer.
[0049] (Formation of bonding layer) An adhesive sheet (CS9862UA, manufactured by Nitto Denko) with a hole of φ25 mm was attached to the lower surface of the second glass layer of the composite to form a bonding layer.
[0050] (Creating a switch device) A rectangular support with an opening as shown in Figure 1 was prepared. The height of the support was 300 mm, and the opening was a cylindrical recess with a diameter of 25 mm. Next, a switch (Alps Alpine Co., Ltd., SKSGAAE010) was placed in the opening, and the bonding layer formed on the composite was attached to the upper surface of the support to produce a switch device with the same structure as in Figure 1. At that time, the part on which the bonding layer was not formed was placed so as to overlap with the opening of the support. The distance between the lower surface of the second glass layer and the switch was 0.2 mm.
[0051] (Evaluation 1: Heat unevenness) The fabricated switch device was evaluated for heat unevenness. That is, the fabricated switch device was left in a heating environment of 90°C for 1 hour, and the composite was evaluated for whether or not unevenness occurred along the edge of the opening. The heat unevenness was evaluated visually, with deformation marked as ◯ and no deformation marked as ×.
[0052] (Rating 2: Push) The composite was deformed in the fabricated switch device, and an evaluation was performed to see if the switch could be pushed in. If the switch could be pushed in (if the switch switched between conductive and non-conductive), it was judged as OK, and if it could not be pushed in (if the switch did not switch between conductive and non-conductive), it was judged as NG.
[0053] [Example 2] A switching device was produced in the same manner as in Example 1 except that the thickness of the first glass layer was 50 μm and the thickness of the PET film was 100 μm, and evaluations were performed in the same manner as in Example 1.
[0054] [Example 3] A switch device was fabricated in the same manner as in Example 1, except that the thickness of the first glass layer was 150 μm, a 25 μm thick PET film (Lumirror T60, manufactured by Toray Industries, Inc.) was used, and the thickness of the second glass layer was 30 μm. The switch device was then evaluated in the same manner as in Example 1.
[0055] [Comparative Example 1] A switching device was produced in the same manner as in Example 1 except that the thickness of the PET film was 188 μm, and evaluation was carried out in the same manner as in Example 1.
[0056] [Comparative Example 2] A switching device was produced in the same manner as in Example 1 except that the thickness of the PET film was 100 μm and the thickness of the second glass layer was 100 μm, and evaluations were performed in the same manner as in Example 1.
[0057] [Reference example] A composite was prepared by bonding a first glass layer having a thickness of 100 μm and a second glass layer having a thickness of 100 μm with an adhesive without providing a resin layer. A switch device was produced in the same manner as in Example 1 except for this, and was evaluated in the same manner as in Example 1.
[0058] [Evaluation Results] The examples, comparative examples, and reference examples are summarized in FIG.
[0059] As shown in Fig. 3, in a configuration without a resin layer such as the reference example, no heating unevenness occurs, but the first glass layer and the second glass layer break and shatter when pressed in. On the other hand, in a configuration with a resin layer between the first glass layer and the second glass layer, the occurrence of heating unevenness and the possibility of pressing in depend on the total thickness of the composite, and it was found that it is preferable for the total thickness of the composite to be 205 µm or less.
[0060] In other words, the inventors discovered that if the total thickness of a composite having a resin layer between a first glass layer and a second glass layer is 205 μm or less, no unevenness occurs when heated, and elastic deformation as a push button is possible.
[0061] Although the preferred embodiments have been described in detail above, the present invention is not limited to the above-described embodiments, and various modifications and substitutions can be made to the above-described embodiments without departing from the scope of the claims.
[0062] In addition to the above-described embodiment, the following supplementary notes are further disclosed. (Appendix 1) a composite including a first glass layer, a resin layer laminated on a lower surface side of the first glass layer, and a second glass layer laminated on a lower surface side of the resin layer; a support portion that is disposed on a lower surface side of the second glass layer of the composite, has an opening, and supports the composite outside the opening; a switch disposed at least partially within the opening; The total thickness of the composite is 230 μm or less, When the complex is pressed, the complex is elastically deformed, causing the switch to switch between conductive and non-conductive states. (Appendix 2) 2. The switching device of claim 1, wherein the composite has a total thickness of 205 μm or less. (Appendix 3) the opening exposes a lower surface of the second glass layer; 3. The switch device according to claim 1, wherein the switch is a tactile switch arranged such that a movable part faces the lower surface of the second glass layer. (Appendix 4) 4. The switch device according to claim 1, wherein the first glass layer has a thickness of 50 μm or more and 150 μm or less. (Appendix 5) 5. The switch device according to claim 1, wherein the second glass layer has a thickness of 30 μm or more and 50 μm or less. (Appendix 6) 6. The switch device according to claim 1, wherein the resin layer has a thickness of 25 μm or more and 100 μm or less. [Explanation of symbols]
[0063] 1 Switching device 10 Complex 11 First glass layer 11a Top side 11b Bottom side 12 Resin layer 13 Second Glass Layer 20 Bonding layer 30 Support part 30x opening 40 Switch
Claims
1. a composite including a first glass layer, a resin layer laminated on a lower surface side of the first glass layer, and a second glass layer laminated on a lower surface side of the resin layer; a support portion that is disposed on a lower surface side of the second glass layer of the composite, has an opening, and supports the composite outside the opening; a switch disposed at least partially within the opening; The total thickness of the composite is 230 μm or less, When the complex is pressed, the complex is elastically deformed, causing the switch to switch between conductive and non-conductive states.
2. The switch device of claim 1 , wherein the composite has a total thickness of 205 μm or less.
3. the opening exposes a lower surface of the second glass layer; The switch device according to claim 1 , wherein the switch is a tactile switch arranged such that a movable part faces the lower surface of the second glass layer.
4. The switch device according to claim 1 , wherein the first glass layer has a thickness of 50 μm or more and 150 μm or less.
5. The switch device according to claim 4 , wherein the second glass layer has a thickness of 30 μm or more and 50 μm or less.
6. The switch device according to claim 5 , wherein the resin layer has a thickness of 25 μm or more and 100 μm or less.
Citation Information
Patent Citations
Switch device
JP2022166480A